A MATHEMATICAL MODEL FOR PREDICTING THE PERSISTENCE AND EFFICACY OF BACILLUS THURINGIENSIS VAR ISRAELENSIS IN RELATION TO WATER POLLUTION - SRIVASTAVA, RINA (Med J Armed Forces India, 1998)
In a simulated field trial, the bead formulation of Bacillus thuringiensis var israelensis (Bti) was found to be more persistent in moderately polluted as compared to highly polluted water. A mathematical model was built up to study the influence of time (independent variable) on larval reduction (dependent variable) in relation to degree of water pollution. Two predictive models for different grades of water pollution were developed, which estimated that the larval mortality in moderately polluted water was likely to decline by 3.79 as compared to 5.02 on an average, in highly polluted water with each passing day.